Patterns of failure in locally advanced female breast carcinoma treated with neoadjuvant chemotherapy followed by surgery and radiotherapy – A prospective study - Shilpi Adhikary; Dibyendu Saha; Bidisha Bandyopadhyay; Chandan Dasgupta; Soham Gangopadhyay; Anjan Bera (Asian Journal of Medical Sciences, 2023)
Background: The use of combined modality therapy including surgery, chemotherapy, and radiotherapy increases five survival rates in stage IIA and stage IIIB disease to 80% and 45%, respectively. Neoadjuvant chemotherapy (NACT) eradicates micro metastasis present in the body and also improves resectability. Aims and Objectives: The main aim of this study was to determine the locoregional recurrence and distant recurrence rates and thereby define clinical and pathological predictive factors for recurrence. Materials and Methods: This was a single institutional prospective study carried out in the Department of Radiotherapy, RG Kar Medical College and Hospital, Kolkata. From January 2017 to December 2019, according to inclusion and exclusions criteria, a total of 1183 histologically and/or cytologically proven breast carcinoma patients were included in this prospective study. Results: Breast conservative surgery was done in 16.5% of patients and the rest of the patients underwent modified radical mastectomy. Seven patients had undergone toilet mastectomy with the specimen. From the pathological review of the surgical specimens, 15.0% of patients achieved pathological complete response, while 19.4% of patients had clinical complete response. A total of 150 patients out of 1183 patients (12.67%) had disease recurrence. Conclusion: Local treatments, either surgery alone and/or RT alone, are inadequate therapies for locally advanced breast cancer patients, and multidisciplinary treatment should be used, to reach better management. Inoperable locally advanced breast carcinoma can be converted into operable by NACT.